Dysregulation of YAP by ARF Stimulated with Tea-derived Carbon Nanodots. Issue 1 (December 2017) - Xie, Yingqiu; Sun, Qinglei; Nurkesh, Ayan; Lu, Jiang; Kauanova, Sholpan; Feng, Jinhong; Tursynkhan, Darkhan; Yang, Qing; Kassymbek, Aishabibi; Karibayev, Mirat; Duisenova, Korlan; Fan, Haiyan; et al.
Abstract YAP is a downstream nuclear transcription factor of Hippo pathway which plays an essential role in development, cell growth, organ size and homeostasis. It was previously identified that elevation of YAP in genomics of genetic engineered mouse (GEM) model of prostate cancer is associated with Pten/Trp53 inactivation and ARF elevation hypothesizing the essential crosstalk of AKT/mTOR/YAP with ARF in prostate cancer. However, the detailed function and trafficking of YAP in cancer cells remains unclear. Using GEM microarray model, we found ARF dysregulates Hippo and Wnt pathways. In particular, ARF knockdown reduced non-nuclear localization of YAP which led to an increase in F-actin. Mechanistically, ARF knockdown suppressed protein turnover of β-catenin/YAP, and therefore enhanced the activity of AKT and phosphorylation of YAP. Moreover, we found tea-derived carbon dots can interact with ARF in nucleus that may further lead to the non-nuclear localization of YAP. Thus, we reported a novel crosstalk of ARF/β-catenin dysregulated YAP in Hippo pathway and a new approach to stimulate ARF-mediated signaling to inhibit nuclear YAP using nanomaterials implicating an innovative avenue for treatment of cancer.